Comment on "A question of method and place? A critical reappraisal of the methods of dendroarchaeology, anthracology, archaeobotany and roundwood analysis on the question when systematic woodland management began in Europe [Quat. Int., in press, https://doi.org/10.1016/j.quaint.2022.05.006]". (10th May 2023) - Out, Welmoed A.; Hänninen, Kirsti; Vermeeren, Caroline
Abstract: Bleicher and Staub's recent review (in press) concerns the discussion of when regular woodland management started in Europe by comparing, amongst others, dendrotypology and age/diameter analysis. In this comment we clarify aspects of age/diameter analysis, present suggestions for dendrotypology and expand the discussion why dendrotypology and age/diameter analysis generate apparently contradictory conclusions about woodland management in the Neolithic, highlighting the relevance of precise definitions.